Melt-processable and foamable cellulose acetate formulations containing natural fillers
By developing a foamable composition containing cellulose acetate, plasticizer, natural filler and physical foaming agent, the non-biodegradable and safety problems of polystyrene foam in food packaging are solved, and the production of biodegradable cellulose acetate foam with suitable density and good performance is achieved.
Patent Information
- Application Number
- CN202380067603.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-23
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-25
AI Technical Summary
Existing polystyrene foams have non-biodegradability and potential health and safety issues in food packaging, and some regions are considering banning such materials.
A foamable composition is developed, comprising 30 wt% to 92 wt% cellulose acetate, 5 wt% to 30 wt% plasticizer, 3 wt% to 40 wt% natural filler, and 0 wt% to 9 wt% physical foaming agent, from which a biodegradable cellulose acetate foam having a density of 0.040 to 0.600 g/cm3 and an average cell size of 20 to 600 microns were prepared.
The production of biodegradable cellulose acetate foam with suitable density, good thermal and mechanical properties is achieved, avoiding the non-biodegradable and potential safety risks of polystyrene foam, while reducing the cost of raw materials.
Smart Images

Figure BDA0005320896150000041 
Figure BDA0005320896150000191 
Figure BDA0005320896150000201
Abstract
Description
Background Art
[0001] Foamed materials can be used in applications such as insulation, food packaging, non-food packaging, and soundproofing. Many food service products are disposable items that are intended to be discarded after the food package has been opened or the food has been consumed. A commercially important material for making foam food packaging products is polystyrene. However, polystyrene is neither compostable nor biodegradable. In addition, some cities, states, and countries have enacted or are considering enacting bans on the use of polystyrene-based foams. In addition to the non-biodegradability of polystyrene, many polystyrene foams also utilize talc as an inorganic physical nucleating agent to initiate the formation of foam cells. The use of talc in products intended for food contact applications may present health and safety issues.
[0002] Cellulose acetate-based foams can be biodegradable and can be used as a substitute for polystyrene foams. However, it is required that cellulose acetate-based foams must exhibit an appropriate density (≤ 0.400 g / cm for low-density applications). 3 , or greater than 0.400 g / cm for medium density applications 3 Up to 1.0g / cm 3 ) and good thermal and mechanical properties. Cellulose acetate-based foams must be processable on commercial extrusion equipment and ideally have the ability to be thermoformed on commercial thermoforming equipment. Natural fillers may also be biodegradable and may act as physical nucleating agents during the foaming process. In addition, due to their hygroscopic nature, natural fillers may act as a carrier for water, which acts as a physical blowing agent during the foaming process, helping to reduce the density of the resulting foam. Because natural fillers are less expensive than cellulose acetate resins, they can simultaneously reduce the raw material cost of cellulose acetate-based foamable compositions while also imparting improved foam properties by acting as physical nucleating agents and / or physical blowing agents. Summary of the invention
[0003] The present application discloses a foamable composition, which comprises 30 wt% to 92 wt% of cellulose acetate, 5 wt% to 30 wt% of at least one plasticizer, 3 wt% to 40 wt% of at least one natural filler, and 0 wt% to 9 wt% of at least one physical foaming agent; wherein the wt% is based on the total weight of all components of the composition. The foamable composition can form a foamable foam with a density of 0.040 to 0.600 g / cm 3 , a biodegradable cellulose acetate foam having an average cell size of 20 to 600 micrometers and an appearance that is easily distinguished from polystyrene foam. The biodegradable cellulose acetate foam can be formed into an article. DETAILED DESCRIPTION
[0004] definition
[0005] It should be understood that the following is not intended to be an exhaustive list of defined terms. Other definitions may be provided in the foregoing description, such as, for example, where context accompanies the use of a defined term.
[0006] As used herein, the terms "a", "an" and "the" mean one or more than one.
[0007] As used herein, the terms "comprising," "comprises," and "comprise" are open transition words that are used to transition from the subject matter recited before the term to one or more elements recited after the term, wherein the one or more elements listed after the transition word are not necessarily the only elements that make up the subject matter.
[0008] Nucleating agent means a chemical or physical material that provides a site for hole formation in the molten formulation mixture. Nucleating agents can include chemical nucleating agents and physical nucleating agents. Nucleating agents can be blended with the formulation introduced into the hopper of the extruder. Alternatively, nucleating agents can be added to the molten resin mixture in the extruder.
[0009] Suitable physical nucleating agents have a desirable particle size. Examples of inorganic physical nucleating agents include, but are not limited to, talc, CaCO , mica and a mixture of at least two of the foregoing substances. A representative example is a talc concentrate based on Heritage Plastics HT6000 linear low density polyethylene (LLDPE). It has been found that biodegradable particulate natural fillers derived from renewable organic sources can also serve as effective physical nucleating agents. Examples of natural fillers that can be used as physical nucleating agents include, but are not limited to, pecan shell powder, walnut shell powder, wood powder, corn cob powder, rice husk powder and oat fiber powder. A representative example of an organic physical nucleating agent is the oat fiber powder commercially available from NuNatural.
[0010] Suitable chemical nucleating agents decompose when the chemical reaction temperature is reached to create pores in the molten formulation. These small pores serve as nucleation sites for larger pore growth from physical or other types of foaming agents. Examples of chemical nucleating agents include, but are not limited to, citric acid or citric acid-based materials. A representative example is HYDROCEROL TM CF-40E (available from Clariant Corporation), which contains citric acid and a crystal nucleating agent.
[0011] A blowing agent refers to a physical or chemical material (or combination of materials) that acts to expand the nucleation site. A blowing agent may include a chemical blowing agent, a physical blowing agent, a combination thereof, or several types of chemical blowing agents and physical blowing agents. A blowing agent is used to reduce density by expanding the holes formed at the nucleation site in a molten formulation. A blowing agent may be added to the molten resin mixture in an extruder. It was unexpectedly found that the hygroscopic properties of biodegradable particulate natural fillers allow them to absorb moisture and carry the absorbed water to the molten resin mixture, where it may act as a physical blowing agent.
[0012] Chemical blowing agents are materials that degrade or react to produce gas. Chemical blowing agents can be endothermic or exothermic. Chemical blowing agents typically degrade at a specific temperature to decompose and release gas. Examples of chemical blowing agents include citric acid, sodium bicarbonate, sodium carbonate, ammonium bicarbonate, ammonium carbonate, etc.
[0013] Examples of physical blowing agents include H2O, N2, CO2, alkanes, alkenes, ethers, ketones, argon, helium, air or mixtures. As described above, hygroscopic biodegradable natural fillers can be formulated into the composition and allowed to absorb moisture prior to the foaming process, wherein the water is then released to act as a physical blowing agent.
[0014] In an embodiment, the cellulose acetate used in the present invention can be any cellulose acetate known in the art and biodegradable. The cellulose acetate that can be used in the present invention generally comprises repeating units of the following structure:
[0015]
[0016] Where R 1 , R 2 and R 3Independently selected from hydrogen or acetyl. For cellulose esters, the substitution level is usually expressed as a degree of substitution (DS), which is the average number of non-OH substituents in each anhydroglucose unit (AGU). In general, conventional cellulose contains three hydroxyl groups that can be substituted in each AGU unit; therefore, the value of DS can be between zero and three. Natural cellulose is a large polysaccharide with a degree of polymerization of 250-5,000 even after pulping and purification, and therefore the assumption that the maximum DS is 3.0 is approximately correct. Since DS is a statistical average, a value of 1 does not guarantee that each AGU has a substituent. In some cases, there may be unsubstituted anhydroglucose units, some with two substituents and some with three substituents, and generally the value will be a non-integer. Total DS is defined as the average number of all substituents per anhydroglucose unit. The degree of substitution of each AGU can also refer to a specific substituent, such as, for example, a hydroxyl or acetyl group. In embodiments, n is an integer ranging from 25 to 250, or from 25 to 200, or from 25 to 150, or from 25 to 100, or from 25 to 75.
[0017] In an embodiment of the present invention, cellulose acetate has at least 2 anhydroglucose rings and may have at least 50 to a maximum of 500 anhydroglucose rings, or at least 50 to less than 150 anhydroglucose rings. The number of anhydroglucose units per molecule is defined as the degree of polymerization (DP) of cellulose acetate. In an embodiment, the cellulose ester may have an intrinsic viscosity (IV) of about 0.2 to about 3.0 deciliters per gram, or about 0.5 to about 1.8, or about 1 to about 1.5, as measured for a 0.25 gram sample in 100 ml of a 60 / 40 weight solution of phenol / tetrachloroethane at a temperature of 25°C. In an embodiment, the cellulose acetate useful herein may have a DS / AGU of about 2.2 to about 2.6, and the substituted ester is an acetyl group.
[0018] Cellulose acetate can be produced by any method known in the art. Examples of processes for producing cellulose esters are taught in Kirk-Othmer, Encyclopedia of Chemical Technology, 5th Edition, Volume 5, Wiley-Interscience, New York (2004), pages 394-444. Cellulose is the starting material for the production of cellulose acetate and can be obtained in different grades and sources, such as from cotton linters, softwood pulp, hardwood pulp, corn fiber and other agricultural sources, and bacterial cellulose, etc.
[0019] One method of producing cellulose acetate is by esterifying the cellulose by mixing it with an appropriate organic acid, anhydride, and catalyst. The cellulose is then converted to a cellulose triester. The esters are then hydrolyzed by adding a water-acid mixture to the cellulose triesters, which can then be filtered to remove any gel particles or fibers. Water is then added to the mixture to precipitate the cellulose esters. The cellulose esters can then be washed with water to remove reaction by-products, followed by dehydration and drying.
[0020] The cellulose triester to be hydrolyzed may have three acetyl substituents. These cellulose esters may be prepared by many methods known to those skilled in the art. For example, cellulose esters may be prepared by heterogeneous acylation of cellulose in a mixture of carboxylic acid and anhydride in the presence of a catalyst such as H2SO4. Cellulose triesters may also be prepared by homogeneous acylation of cellulose dissolved in a suitable solvent such as LiCl / DMAc or LiCl / NMP.
[0021] Those skilled in the art will appreciate that the commercial term cellulose triesters also encompass cellulose esters that are not fully substituted with acyl groups. For example, cellulose triacetate commercially available from Eastman Chemical Company, Kingsport, TN, USA, typically has a DS of about 2.85 to about 2.99.
[0022] After cellulose is esterified to triesters, some of the acyl substituents may be removed by hydrolysis or by alcoholysis to obtain secondary cellulose esters. As previously mentioned, the distribution of the acyl substituents may be random or non-random, depending on the particular method employed. Secondary cellulose esters may also be prepared directly without hydrolysis by using a limited amount of acylating agent. This method is particularly useful when the reaction is carried out in a solvent that will dissolve the cellulose. All of these methods produce cellulose esters useful in the present invention.
[0023] In one embodiment or in combination with any of the mentioned embodiments, the cellulose acetate is cellulose diacetate having a polystyrene equivalent number average molecular weight (Mn) of about 10,000 to about 100,000 as measured by gel permeation chromatography (GPC) using NMP as solvent and according to ASTM D6474. In an embodiment, the cellulose acetate composition comprises cellulose diacetate having a polystyrene equivalent number average molecular weight (Mn) of about 10,000 to about 100,000 as measured by gel permeation chromatography (GPC) using NMP as solvent and according to ASTM D6474. 10,000 to 90,000; or 10,000 to 80,000; or 10,000 to 70,000; or 10,000 to 60,000; or 10,000 to less than 60,000; or 10,000 to less than 55,000; or 10,000 to 50,000; or 10,000 to less than 50,000; or 10,000 to less than 45,000; or 10,000 to 40,000; or 10,000 to 30,000; or 20,000 to less than 60,000; or 20,000 to less than 55,000; or 20, or 30,000 to less than 60,000; or 30,000 to less than 55,000; or 30,000 to 50,000; or 30,000 to less than 50,000; or 30,000 to less than 45,000; or 20,000 to 40,000; or 20,000 to 35,000; or 20,000 to 30,000; or 30,000 to less than 60,000; or 30,000 to less than 55,000; or 30,000 to 50,000; or 30,000 to less than 50,000; or 30,000 to less than 45,000; or 30,000 to 40,000; or 30,000 to 35,000.
[0024] The most common commercial secondary cellulose esters are prepared by an initial acid-catalyzed heterogeneous acylation of cellulose to form cellulose triesters. After obtaining a homogeneous solution of the cellulose triesters in the corresponding carboxylic acids, the cellulose triesters are then hydrolyzed until the desired degree of substitution is obtained. After separation, random secondary cellulose esters are obtained. That is, the relative degree of substitution (RDS) of each hydroxyl group is approximately equal.
[0025] The cellulose acetate used in the present invention can be prepared using techniques known in the art and can be selected from various types of cellulose esters, such as, for example, cellulose esters available from Eastman Chemical Company, Kingsport, TN, USA, such as Eastman TM Cellulose acetate CA 398-30 and Eastman TM FE700.
[0026] In embodiments of the invention, cellulose may be prepared by converting cellulose to cellulose esters using reactants obtained from recycled materials (e.g., recycled plastic content syngas sources). In embodiments, such reactants may be cellulosic reactants including organic acids and / or anhydrides used in esterification or acylation reactions of cellulose, e.g., as discussed herein.
[0027] In one embodiment of the invention or in combination with any of the mentioned embodiments or in combination with any of the mentioned embodiments, a cellulose acetate composition is provided comprising at least one recycled cellulose acetate, wherein the cellulose acetate has at least one substituent on an anhydroglucose unit (AU) derived from recycled content material (e.g., recycled plastic content syngas).
[0028] The present application discloses a biodegradable cellulose acetate foam, which contains a biodegradable particulate natural filler, wherein the foam has a carbon content of 0.04 to 0.6 g / cm 3 The density is 20 μm to 600 μm, and the average cell size is 20 μm to 600 μm.
[0029] In one embodiment or in combination with any of the embodiments mentioned herein, the foam has a viscosity of 0.04 to 0.6 g / cm 3 , or 0.04 to 0.5 g / cm 3 , or 0.04 to 0.4 g / cm 3 , or 0.04 to 0.3 g / cm 3 , or 0.04 to 0.2 g / cm 3 , or 0.04 to 0.1 g / cm 3 , or 0.06 to 0.6 g / cm 3 , or 0.06 to 0.5 g / cm 3 , or 0.06 to 0.4 g / cm 3 , or 0.06 to 0.3 g / cm 3 , or 0.06 to 0.2 g / cm 3 , or 0.06 to 0.1 g / cm 3 , or 0.08 to 0.6 g / cm 3 , or 0.08 to 0.5 g / cm 3 , or 0.08 to 0.4 g / cm 3 , or 0.08 to 0.3 g / cm 3 , or 0.08 to 0.2 g / cm 3 , or 0.08 to 0.1 g / cm 3 , or 0.1 to 0.6 g / cm 3 , or 0.1 to 0.5 g / cm 3 , or 0.1 to 0.4 g / cm3 , or 0.1 to 0.3 g / cm 3 , or 0.1 to 0.2 g / cm 3 , or 0.2 to 0.6 g / cm 3 , or 0.2 to 0.5 g / cm 3 , or 0.2 to 0.4 g / cm 3 , or 0.2 to 0.3 g / cm 3 , or 0.3 to 0.6 g / cm 3 , or 0.3 to 0.5 g / cm 3 , or 0.3 to 0.4 g / cm 3 , or 0.4 to 0.6 g / cm 3 , or 0.4 to 0.5 g / cm 3 or 0.5 to 0.6 g / cm 3 density.
[0030] In one embodiment or in combination with any embodiment mentioned herein, the average cell size is 40 μm to 600 μm, or 50 μm to 600 μm, or 60 μm to 600 μm, or 70 μm to 600 μm, or 80 μm to 600 μm, or 90 μm to 600 μm, or 100 μm to 600 μm, or 150 μm to 600 μm, or 200 μm to 600 μm, or 250 μm to 600 μm, or 300μm to 600μm, or 400μm to 600μm, or 500μm to 600μm, or 40μm to 550μm, or 40μm to 500μm, or 40μm to 450μm, or 40μm to 400μm, or 40μm to 350μm, or 40μm to 300μm, or 40μm to 250μm, or 40μm to 200μm, or 40μm to 150μm or 40μm to 100μm.
[0031] In one embodiment or in combination with any of the embodiments mentioned herein, the foam is prepared from a composition comprising: (a) 30 wt% to 92 wt% cellulose acetate; (b) 5 wt% to 30 wt% plasticizer; (c) 3.0 wt% to 40 wt% of at least one natural filler; and (d) 0.0 wt% to 9 wt% of at least one physical blowing agent; wherein the wt% are based on the total weight of all components of the composition.
[0032] In one embodiment or in combination with any of the embodiments mentioned herein, the cellulose acetate has a degree of acetyl substitution (DS Ac ).
[0033] In one embodiment or in combination with any embodiment mentioned herein, plasticizer comprises triacetin, triethyl citrate or the polyethylene glycol of average weight average molecular weight being 300 to 1000Da.In a category of this embodiment, plasticizer comprises triacetin.In a category of this embodiment, plasticizer comprises triethyl citrate.In a category of this embodiment, plasticizer comprises polyethylene glycol of average weight average molecular weight being 300 to 1000Da.In a subclass of this category, polyethylene glycol has the average weight average molecular weight of 300 to 500Da.In a subclass of this category, polyethylene glycol has the average weight average molecular weight of 400Da.
[0034] In one embodiment or in combination with any of the embodiments mentioned herein, the natural filler is a biodegradable particulate material derived from a renewable organic source. Examples of natural fillers include, but are not limited to, pecan shell meal, walnut shell meal, wood meal, corn cob meal, rice husk meal, oat fiber meal, or a combination thereof.
[0035] In one embodiment or in combination with any of the embodiments mentioned herein, the foamable composition further comprises an inorganic physical nucleating agent.
[0036] In one embodiment or in combination with any of the embodiments mentioned herein, the foamable composition further comprises no inorganic physical nucleating agent.
[0037] In one embodiment or in combination with any of the embodiments mentioned herein, the composition further comprises a second physical blowing agent selected from (C 1-3 )alkyl)2O, CO2, N2, ((C 1-3 )alkyl)2CO, (C 1-6 )alkanol, (C 4-6 ) olefins or combinations thereof. In one class of this embodiment, the second physical blowing agent is ((C 1-3 In one class of this embodiment, the second physical blowing agent is CO2. In one class of this embodiment, the second physical blowing agent is N2. In one class of this embodiment, the second physical blowing agent is ((C 1-3 )alkyl)2CO. In one class of this embodiment, the second physical blowing agent is (C 1-6 In one class of this embodiment, the second physical blowing agent is (C 4-6 )Olefins.
[0038] In one embodiment or in combination with any of the embodiments mentioned herein, the second physical blowing agent is present at 0.2wt% to 3wt%, or 0.2wt% to 2.5wt%, or 0.2wt% to 2wt%, or 0.2wt% to 1.5wt%, or 0.2wt% to 1wt%, or 0.2wt% to 0.5wt%, or 0.5wt% to 3wt%, or 0.5wt% to 2.5wt%, or 0.5wt% to 2wt%, or 0.5wt% to 1.5wt%, or 0.5wt% to 1wt%, or 1wt% to 3wt%, or 1wt% to 2.5wt%, or 1wt% to 2wt%, or 1wt% to 1.5wt%, or 1.5wt% to 3wt%, or 1.5wt% to 2.5wt%, or 1.5wt% to 2wt%, or 2wt% to 3wt%.
[0039] In one embodiment or in combination with any embodiment mentioned herein, plasticizer comprises triacetin, triethyl citrate or the polyethylene glycol of average weight average molecular weight being 300 to 1000Da.In a category of this embodiment, plasticizer comprises triacetin.In a category of this embodiment, plasticizer comprises triethyl citrate.In a category of this embodiment, plasticizer comprises polyethylene glycol of average weight average molecular weight being 300 to 1000Da.In a subclass of this category, polyethylene glycol has the average weight average molecular weight of 300 to 500Da.In a subclass of this category, polyethylene glycol has the average weight average molecular weight of 400Da.
[0040] In one embodiment or in combination with any of the embodiments mentioned herein, the inorganic physical nucleating agent comprises a particulate composition having a median particle size of less than 2 microns. In one class of this embodiment, the physical nucleating agent comprises a particulate composition having a median particle size of 0.1 to 2 microns. In one class of this embodiment, the physical nucleating agent comprises a particulate composition having a median particle size of 0.5 to 2 microns. In one class of this embodiment, the physical nucleating agent comprises a particulate composition having a median particle size of 1 to 2 microns.
[0041] In one embodiment or in combination with any of the embodiments mentioned herein, the inorganic physical nucleating agent comprises magnesium silicate, silicon dioxide, magnesium oxide, or a combination thereof.
[0042] In one embodiment or in combination with any embodiment mentioned herein, the organic physical nucleating agent comprises a biodegradable particulate natural filler having a maximum particle size of less than or equal to 600 microns. In one category of this embodiment, the organic physical nucleating agent comprises a biodegradable particulate natural filler having a maximum particle size of less than or equal to 250 microns. In one category of this embodiment, the organic physical nucleating agent comprises a biodegradable particulate natural filler having a maximum particle size of less than or equal to 180 microns. In one category of this embodiment, the organic physical nucleating agent comprises a biodegradable particulate natural filler having a maximum particle size of less than or equal to 150 microns. In one category of this embodiment, the organic physical nucleating agent comprises a biodegradable particulate natural filler having a maximum particle size of less than or equal to 75 microns. In one category of this embodiment, the organic physical nucleating agent comprises a biodegradable particulate natural filler having a maximum particle size of less than or equal to 60 microns.
[0043] In one embodiment or in combination with any embodiment mentioned herein, the organic physical nucleating agent comprises a biodegradable particulate natural filler. Examples of biodegradable particulate natural fillers include, but are not limited to, pecan shell meal, walnut shell meal, wood meal, corn cob meal, rice husk meal, oat fiber meal, or a combination thereof.
[0044] In one embodiment or in combination with any of the embodiments mentioned herein, the foam, composition or foamable composition comprises two or more cellulose acetates having different degrees of acetyl substitution.
[0045] In one embodiment or in combination with any of the embodiments mentioned herein, the first physical blowing agent is 1.3 wt% to 1.5 wt%, or 1.3 wt% to 2.0 wt%, or 1.3 wt% to 2.5 wt%, or 1.3 wt% to 3.0 wt%, or 1.3 wt% to 3.5 wt%, or 1.3 wt% to 4.0 wt%, or 1.3 wt% to 4.5 wt%, or 1.3 wt% to 5.0 wt%, or 1.3 wt% to 5.5 wt%. %, or 1.5wt% to 3.0wt%, or 1.5wt% to 4.0wt%, or 1.5wt% to 5.0wt%, or 1.5wt% to 6.0wt%, or 2.0wt% to 3.0wt%, or 2.0wt% to 4.0wt%, or 2.0wt% to 5.0wt%, or 2.0wt% to 6.0wt%, or 2.5wt% to 3.0wt%, or 2.5wt% to 4.0wt%, or 2.5wt% to 5.0wt% %, or 2.5wt% to 6.0wt%, or 3.0wt% to 4.0wt%, or 3.0wt% to 5.0wt%, or 3.0wt% to 6.0wt%, or 0.0wt% to 9.0wt%, or 0.5wt% to 9.0wt%, or 1.0wt% to 9.0wt%, or 1.5wt% to 9.0wt%, or 2.0wt% to 9.0wt%, or 2.5wt% to 9.0wt%, or 3.0wt% to 9.0wt%, Or 3.5wt% to 9.0wt%, or 4.0wt% to 9.0wt%, or 4.5wt% to 9.0wt%, or 5.0wt% to 9.0wt%, or 5.5wt% to 9.0wt%, or 6.0wt% to 9.0wt%, or 6.5wt% to 9.0wt%, or 7.0wt% to 9.0wt%, or 7.5wt% to 9.0wt%, or 8.0wt% to 9.0wt% or 8.5wt% to 9.0wt% is present.
[0046] In one embodiment or in combination with any of the embodiments mentioned herein, the physical nucleating agent is present at 0.1 wt% to 2.5 wt%, or 0.1 wt% to 2.0 wt%, or 0.1 wt% to 1.5 wt%, or 0.1 wt% to 1.0 wt%, or 0.1 wt% to 0.5 wt%, or 0.1 wt% to 5.0 wt%, or 0.1 wt% to 10.0 wt%, or 0.1 wt% to 20.0 wt%, or 0.1 wt% to 30.0 wt%, or 0.1 wt% to 40.0 wt%, or 0.2 wt% to 3.0 wt%, or 0.2 wt% to 2.5 wt%, or 0.2 wt% to 2.0 wt%, or 0.2 wt% to 1.5 wt%, or 0.2 wt% to 1.0wt%, or 0.2wt% to 0.5wt%, or 0.5wt% to 2.5wt%, or 0.5wt% to 2.0wt%, or 0.5wt% to 1.5wt%, 0.5wt% to 1.0wt%, or 1.0wt% to 6.0wt%, or 1.0wt% to 5.5wt%, or 1.0wt% to 5.0wt%, 1.0wt% to 4.5wt%, or 1.0wt% to 4.0wt%, or 1.0wt% to 3.5wt%, or 1.0wt% to 3.0wt%, or 1.0wt% to 2.5wt%, or 1.0wt% to 2.0wt%, or 1.0wt% to 1.5wt%, or 1.5wt% to 6.0wt%, % to 4.5wt%, or 1.5wt% to 4.0wt%, or 1.5wt% to 3.5wt%, or 1.5wt% to 3.0wt%, or 1.5wt% to 2.5wt%, or 1.5wt% to 2.0wt%, or 2.0wt% to 6.0wt%, or 2.0wt% to 5.5wt%, or 2.0wt% to 5.0wt%, or 2.0wt% to 4.5wt%, or 2.0wt% to 4.0wt%, or 2.0wt% to 3.5wt%, or 2.0wt% to 3.0wt%, or 2.0wt% to 2.5wt%, or 2.5wt% to 6.0wt%, .0wt%, or 2.5wt% to 5.5wt%, or 2.5wt% to 5.0wt%, or 2.5wt% to 4.5wt%, or 2.5wt% to 4.0wt%, or 2.5wt% to 3.5wt%, or 2.5wt% to 3.0wt%, or 3.0wt% to 6.0wt%, or 3.0wt% to 5.5wt%, or 3.0wt% to 5.0wt%, or 3.0wt% to 4.5wt%, or 3.0wt% to 4.0wt%, or 3.0wt% to 3.5wt%, or 3.5wt% to 6.0wt%, or 3.5wt% to 5.5wt%, or 3.5wt% to 5.0wt%, or 3.5wt% to 4.5wt%, or 3.5wt% to 4.0wt%, or 4.0wt% to 6.0wt%, or 4.0wt% to 5.5wt%, or 4.0wt% to 5.0wt%, or 4.0wt% to 4.5wt%, or 4.5wt% to 6.0wt%, or 4.5wt% to 5.5wt% or 4.5wt% to 5.0wt%. .
[0047] In one embodiment or in combination with any of the embodiments mentioned herein, the plasticizer is from 5wt% to 30wt%, or 5wt% to 25wt%, or 5wt% to 20wt%, or 5wt% to 15wt%, or 5wt% to 10wt%, or 6wt% to 30wt%, or 6wt% to 25wt%, or 6wt% to 20wt%, or 6wt% to 15wt%, or 6wt% to 10wt%, or 7wt% to 30wt%, or 7wt% to 25wt%, or 7wt% to 20wt%, or 7wt% to 15wt%, or 7wt% to 10wt%, or 8wt% to 30wt%, or 8wt% to 25wt%, or 8wt% to 20wt%. %, or 8wt% to 15wt%, or 8wt% to 10wt%, or 9wt% to 30wt%, or 9wt% to 25wt%, or 9wt% to 20wt%, or 8wt% to 15wt%, or 9wt% to 30wt%, or 9wt% to 25wt%, or 9wt% to 20wt%, or 9wt% to 15wt%, or 10wt% to 30wt%, or 10wt% to 25wt%, or 10wt% to 20wt%, or 10wt% to 15wt%, or 15wt% to 30wt%, or 15wt% to 25wt%, or 15wt% to 20wt%, or 20wt% to 30wt%, or 20wt% to 25wt%.
[0048] In one embodiment or in combination with any of the embodiments mentioned herein, the foamable composition may be in the form of pellets or powder.
[0049] Disclosed herein are articles made from any of the mentioned biodegradable cellulose acetate foams or compositions disclosed herein.
[0050] To be considered "compostable", a material must meet the following four criteria: (1) the material should pass the biodegradation requirement in a test at elevated temperature (58°C) under controlled composting conditions according to ISO 14855-1 (2012), which corresponds to an absolute 90% biodegradation or a relative 90% biodegradation relative to a control polymer; (2) the material must achieve 90% disintegration when tested under aerobic composting conditions according to ISO 16929 (2013); (3) the tested material must meet all requirements for volatile solids, heavy metals, and fluorine as specified in ASTM D6400 (2012), EN 13432 (2000), and ISO 17088 (2012); and (4) the material should not have a negative impact on plant growth. As used herein, the term "biodegradable" generally refers to the biological transformation and consumption of organic molecules. Biodegradability is an inherent property of the material itself, and materials can exhibit varying degrees of biodegradability, depending on the specific conditions to which they are exposed. The term "disintegrable" refers to the tendency of a material to physically break down into smaller pieces when exposed to specific conditions. The degree of disintegration depends on the material itself as well as the physical size and configuration of the article being tested. Ecotoxicity measures the effect of a material on plant life and the heavy metal content of a material is determined according to procedures specified in standard test methods.
[0051] According to French norm NF T 51-800 and Australian standard AS 5810, to be considered "biodegradable" under home composting conditions, a material must show a total biodegradation of at least 90% (e.g. compared to the initial sample), or at least 90% of the maximum degradation of a suitable reference material after both the reference and test articles have reached a stationary period. The maximum test duration for biodegradation under home composting conditions is 1 year.
[0052] According to ASTM D6400 and ISO 17088, to be considered "biodegradable" under industrial composting conditions, at least 90% of the organic carbon in the whole article (or for each component present in an amount greater than 1% by dry mass) must be converted to carbon dioxide at the end of the test period when compared to a control or an absolute value. According to European Standard ED 13432 (2000), a material must show a total biodegradation of at least 90%, or a biodegradation of at least 90% of the maximum degradation of a suitable reference material after both the reference article and the test article have reached a stationary phase. The maximum test duration for biodegradability under industrial composting conditions is 180 days.
[0053] according to According to the OK Biodegradable Soil conformity mark and the DIN Geprüft Soil Biodegradability certification scheme of DIN CERTCO, to be considered "biodegradable" under soil composting conditions, a material must show a total biodegradation of at least 90% (e.g. compared to the initial sample) or a biodegradation of at least 90% of the maximum degradation of a suitable reference material after both the reference article and the test article have reached a stabilization period. The maximum test duration for biodegradability under soil composting conditions is 2 years.
[0054] In one embodiment or in combination with any embodiment mentioned herein, the biodegradable cellulose acetate foam or article is industrially compostable or home compostable. In a subclass of this category, the foam or article is industrially compostable. In a sub-subclass of this subclass, the foam or article has a thickness of less than 6 mm. In a sub-subclass of this subclass, the foam or article has a thickness of less than 3 mm. In a sub-subclass of this subclass, the article has a thickness of less than 1.1 mm. In a subclass of this category, the foam or article is home compostable. In a sub-subclass of this subclass, the foam or article has a thickness of less than 6 mm. In a sub-subclass of this subclass, the foam or article has a thickness of less than 3 mm. In a sub-subclass of this subclass, the foam or article has a thickness of less than 1.1 mm. In a sub-subclass of this subclass, the foam or article has a thickness of less than 0.8 mm. In a sub-subclass of this subclass, the foam or article has a thickness of less than 0.6 mm. In a sub-subclass of this subclass, the foam or article has a thickness of less than 0.4 mm.
[0055] In one embodiment or in combination with any of the embodiments mentioned herein, the foam or article has a thickness of less than 3 mm.
[0056] In one embodiment or in combination with any embodiment mentioned herein, the foam or article exhibits greater than 90% disintegration after 12 weeks according to the Disintegration Test Protocol for Films described in this specification.
[0057] The composition for preparing the biodegradable cellulose acetate foam may include other additives such as fillers, stabilizers, odor regulators, waxes, extenders, biodegradation promoters, dyes, pigments, colorants, lubricants, antioxidants, viscosity regulators, antifungal agents, thermal stabilizers, antibacterial agents, softeners, release agents, and combinations thereof. It should be noted that the same type of compound or material may be identified as or included in multiple classes of components in the cellulose acetate composition. For example, polyethylene glycol (PEG) may be used as a plasticizer or as an additive that does not act as a plasticizer, such as a hydrophilic polymer or a biodegradation promoter, for example, where a lower molecular weight PEG has a plasticizing effect, while a higher molecular weight PEG acts as a hydrophilic polymer but has no plasticizing effect.
[0058] In one embodiment or in combination with any embodiment mentioned herein, the foam, composition or foamable composition further comprises a photodegradation catalyst. In a class of this embodiment, the photodegradation catalyst is titanium dioxide or iron oxide. In a subclass of this class, the photodegradation catalyst is titanium dioxide. In a subclass of this class, the photodegradation catalyst is iron oxide.
[0059] In one embodiment or in combination with any embodiment mentioned herein, the foam, composition or foamable composition further comprises a pigment. In one category of this embodiment, the pigment is titanium dioxide, carbon black or iron oxide. In a subcategory of this category, the pigment is titanium dioxide. In a subcategory of this category, the pigment is carbon black. In a subcategory of this category, the pigment is iron oxide. In a subcategory of this category, the pigment is a biodegradable particulate natural filler.
[0060] The claims are not limited to the disclosed embodiments
[0061] The preferred forms of the present invention described above are intended to be used as illustrations only and should not be used in a limiting sense to interpret the scope of the present invention. Those skilled in the art may easily make modifications to the above exemplary embodiments without departing from the spirit of the present invention.
[0062] The inventors hereby declare that they intend to determine and assess the reasonable and fair scope of the present invention under the doctrine of equivalents as it relates to any device that does not materially depart from the literal scope of the present invention as set forth in the following claims.
[0063] In one embodiment or in combination with any other embodiment, the foam or article exhibits greater than 30% disintegration after 12 weeks according to the disintegration test protocol described in this specification or according to the alternatives to ISO 16929 (2013). In one embodiment or in combination with any other embodiment, the foam or article exhibits greater than 50% disintegration after 12 weeks according to the disintegration test protocol described in this specification or according to the alternatives to ISO 16929 (2013). In one embodiment or in combination with any other embodiment, the foam or article exhibits greater than 70% disintegration after 12 weeks according to the disintegration test protocol described in this specification or according to the alternatives to ISO 16929 (2013). In one embodiment or in combination with any other embodiment, the foam or article exhibits greater than 80% disintegration after 12 weeks according to the disintegration test protocol described in this specification or according to the alternatives to ISO 16929 (2013). In one embodiment or in combination with any other embodiment, the foam or article exhibits greater than 90% disintegration after 12 weeks according to the disintegration test protocol described in this specification or according to the alternative protocol of ISO 16929 (2013). In one embodiment or in combination with any other embodiment, the foam or article exhibits greater than 95% disintegration after 12 weeks according to the disintegration test protocol described in this specification or according to the alternative protocol of ISO 16929 (2013).
[0064] Example
[0065] For the examples herein, the test methods, abbreviations and materials are as follows:
[0066] Color is reported as CIE color space L*a*b* values measured using a colorimeter (Konica Minolta CR-400). Color is represented by: L*, where 0=black and 100=white; a*, where negative values represent green and positive values represent red; b*, where negative values represent blue and positive values represent yellow. To measure the color of a film sample, a piece of 10 mil film was placed on white cardboard as a background. To measure the color of a filler sample, an amount of filler sufficient to prevent penetration through a microscope slide was sandwiched between a microscope slide and a cover glass.
[0067] Particle sizes are reported in microns as the upper (not exceeding) particle size based on standard U.S. mesh size.
[0068] The film thickness was determined by the thickness of the frame used to compression mold the film sample. The thickness of the frame used was either 254 microns (10 mils) or 508 microns (20 mils).
[0069] Tensile properties were measured according to ASTM-D638 on an Instron tensile test frame. Break stress and Young's modulus are reported in MPa, break strain is reported in %, and break energy is reported in N / mm 2 Report.
[0070] Density is measured by the water displacement method, where the sample is immersed in water and the volume of water displaced (cm 3 ) Record the mass (g) of a foam sample approximately 1 cm x 3 cm before weighing. Density is calculated by dividing the mass by the volume.
[0071] The pore size was determined by capturing cross-sectional images of the foam samples prepared by the microtome at 90° using a scanning electron microscope at 1000 times magnification. The diameters of at least 10 randomly selected pores were then measured using digital image analysis software (ImageJ). The average of the measured diameters was recorded as the sample pore size.
[0072] Weight % may be abbreviated as wt % and, unless otherwise indicated, is based on the weight of all other components (both solid and liquid) in the formulation.
[0073] Cellulose Acetate (CA)
[0074] CA1: CA-398-30 (39.7 wt% acetyl); commercially available from Eastman Chemical Company
[0075] CA2: Cellulose acetate FE700 (40 wt% acetyl); commercially available from Eastman Chemical Company
[0076] Liquid plasticizer
[0077] TEC - Triethyl citrate 98% – CAS No. 77-93-0; MW: 276.28; commercially available from Sigma Aldrich, product number 27500
[0078] TA-Triacetin – Commercially available from Eastman Chemical Company
[0079] Natural fillers
[0080] NF1 – Pecan Shell Powder – Particle Size: ≤74 μm (200 mesh); commercially available from Composition Materials Co., Inc.
[0081] NF2 – Walnut shell powder – Particle size: ≤149 μm (100 mesh); commercially available from Composition Materials Co., Inc.
[0082] NF3 - Wood Flour 30 / 60 - Particle Size: 50% ≤ 600 μm (30 mesh) and 50% ≤ 250 μm (60 mesh); commercially available from Composition Materials Co., Inc.
[0083] NF4 - Wood Flour 60 - Particle Size: ≤250 μm (60 mesh); commercially available from Composition Materials Co., Inc.
[0084] NF5 – Corncob Biofiller – Particle size: ≤177 μm (80 mesh); commercially available from Composition Materials Co., Inc.
[0085] NF6 – Rice Husk Biofiller – Particle Size: ≤177 μm (80 mesh); commercially available from Composition Materials Co., Inc.
[0086] NF7 - Oat Fiber Powder - Particle size: ≤ 57 μm; commercially available from NuNatural.
[0087] NF8 – Hemp Fiber – Fiber Length: Up to 6mm
[0088] Inorganic physical nucleating agent (IPNA)
[0089] Talc – Talc ABT 1000; commercially available from Specialty Minerals
[0090] Melt Processing Solutions for CA Film / Foam Preforms
[0091] The compounded pellets are formed from CA powder, liquid plasticizer, natural filler and optional inorganic physical nucleating agent. The dry ingredients are bag blended into a free-flowing powder, which is fed into an 18 mm (Leistritz) twin screw extruder with a single hole die. The liquid plasticizer is fed into Zone 2 of the extruder through a syringe with a 0.020 inch hole via a liquid injection unit supplied by a Witte gear pump and controlled by a Hardy 4060 controller. The compounded strands are passed through a water trough and granulated with a ConAir granulator. The pellets are dried overnight in a vacuum oven at 70°C under vacuum at 7-10 psi vacuum.
[0092] The dried pellets were then converted into film samples by compression molding the dried pellets into films using a compression molding machine (Pasadena Hydraulics Inc, PW-220-C-X1-4) and a molding frame with a thickness of 254 microns (10 mils) or 508 microns (20 mils). The samples were molded at a temperature of 400°F (204.4°C) with a punch pressure of 8,000-10,000 pounds for 90 seconds. The pressure was then released and reapplied at a punch pressure of 20,000-22,000 pounds for 30 seconds. The pressure was released again and reapplied at 20,000-22,000 pounds for a final 60 seconds.
[0093] Foaming Solutions
[0094] The batch foaming of the film samples was carried out in a 300mL autoclave (Parr Instrument Company Model 4561) with a diameter of 2.5 inches and a depth of 4 inches. The autoclave was equipped with a thermocouple and a pressure sensor. The dip tube, stirring shaft and impeller were removed. The CA film samples (film thickness of 10 or 20 mils, as shown in Table 1) with a size of 1 inch x 1 inch were placed on a folded Teflon tray with a size of 1.5 inches x 1.5 inches x 0.5 inches (LxWxH). The trays containing the film samples were stacked 3 or 4 layers high in the autoclave in a staggered manner, and the autoclave was then closed, sealed and heated to a desired temperature in the range of 150°C to 230°C. Once the autoclave reached the desired temperature, the container was pressurized to a desired pressure in the range of 50 bar to 130 bar with CO2 gas, and the autoclave was stabilized at the target temperature and pressure. After stabilization, the CA film samples were kept at the target temperature and pressure for 30 minutes to allow the CO2 gas to penetrate into the film. After 30 minutes at the target temperature and pressure, the 1 / 4" vent valve was opened and the autoclave was purged with nitrogen. The rapid pressure release caused the film sample to expand into a foam. After the autoclave cooled to room temperature, the foam sample was removed and analyzed for density (g / cm 3 ) and pore size (nm).
[0095] Table 1. Sample formulations and processing conditions
[0096]
[0097]
[0098]
[0099] Example 1 - Filler as Natural Color Additive
[0100] The color of samples of natural fillers was evaluated. The natural fillers evaluated included pecan shell flour (NF1); walnut shell flour (NF2); wood flour 30 / 60 (NF3); wood flour 60 (NF4); corn cob flour (NF5); rice husk flour (NF6); and oat fiber flour (NF7). Following the melt processing scheme described above, film samples with a thickness of 508 microns were produced according to the formulations described in Table 1 Samples 1-8. The color of the resulting films was analyzed. Table 2 summarizes the L*, a*, and b* values measured by a colorimeter.
[0101] Table 2. Color analysis of natural filler materials and CA films with 10% natural filler material loading
[0102]
[0103] As shown in Table 2, all filler and film samples exhibit positive a* values (indicating a red hue) and positive b* values (indicating a yellow hue). For most films, the color becomes more vivid as indicated by the higher a* and b* values. After melt processing, the film samples generally exhibit lower L* values, indicating that the filler color is darker than that exhibited before melt processing. The film of sample 4 (NF3) does not appear darker (lower L*) or have higher a* and b* values, showing significant agglomeration of the filler, resulting in a mottled appearance with distinct light and dark areas, which may result in a substandard color result for this sample. Samples 1-8 demonstrate that incorporating natural fillers into CA films is an effective means of generating CA films and foam / foamed articles with natural colors, which cannot be obtained with commercially popular compositions utilizing polystyrene, plasticizers, and talc. The natural appearance of the foam products of samples 2-8 is the result of using natural fillers and is desirable because it is easily distinguished from articles made of non-biodegradable white polystyrene-based foamed polystyrene.
[0104] Example 2 - Tensile Properties of CA Films Containing Natural Fillers
[0105] The pellets were compounded and compression molded into film samples according to the above melt processing scheme and the formulations listed in Table 1, Samples 9 to 16. The resulting 508 micron thick films were conditioned at 25°C and 50% RH for 48 hours and then tested for tensile properties according to ASTM-D638.
[0106] Table 3. Tensile properties of 508 μm thick films containing 10% natural filler
[0107]
[0108] As the maximum particle size of the natural filler increases, the fracture stress and Young's modulus tend to decrease, while the fracture strain and fracture energy do not seem to be affected by the particle size. Comparing the microparticle fillers (samples 9-15) with the hemp fiber filler (sample 16), the films with microparticle natural fillers appear to be more ductile, showing higher fracture strain and fracture energy.
[0109] Example 3 - Intermittent Foaming of CA Films with Natural Fillers and Talc
[0110] The pellets were compounded and compression molded into films having a thickness of 254 microns according to the melt processing protocol described above and the formulations listed in Table 1, Samples 17-24.
[0111] Batch foaming of the film samples was carried out according to the foaming protocol described above using a pressure of 130 bar and a temperature of 200° C. The density and cell size of the foam samples were measured and are summarized in Table 4 below.
[0112] Table 4. Density and cell size of CA foams with natural fillers and 1% talc
[0113]
[0114] These results demonstrate that cellulose acetate compositions containing various types of natural fillers and talc can be converted into cellulose acetate foam samples that exhibit densities and cell sizes useful for many low density foam product applications.
[0115] Example 4 - Talc-free foam formulation with high natural filler content
[0116] Films containing various types of natural fillers and no inorganic physical nucleating agent were prepared according to the above melt processing scheme and the formulations listed in Table 1, Samples 25-39. The obtained film samples were foamed according to the foaming scheme at the pressure and temperature listed in Table 1. All samples did not contain an inorganic physical nucleating agent. The density and pore size of the foam samples were measured and the obtained density and pore size are summarized in Table 5 below.
[0117] Table 5. Foams with high natural filler content and without inorganic physical nucleating agents
[0118]
[0119]
[0120] *Samples exhibit density suitable for medium density foam applications
[0121] Not only do natural fillers change the appearance of the cellulose acetate composition and the resulting foam, but they also act as physical nucleating agents, thereby eliminating the need for inorganic physical nucleating agents such as talc. In addition, low density foams with high natural filler loadings can be produced, thereby reducing the overall raw material cost of the composition. For example, less than 0.400 g / cm 3 Acceptable low density foams can be achieved with up to 30% loading of oat fiber powder or wood flour without using any inorganic physical nucleating agents.
[0122] Example 5 - Natural fillers to reduce CA foam density
[0123] Natural fillers are hygroscopic and can serve as a carrier for water, which acts as a physical blowing agent during the foaming process to reduce the foam density.
[0124] To evaluate the equilibrium moisture absorption of natural fillers, a sample of each natural filler material was dried overnight under vacuum. The samples were weighed after drying and the weight loss % was attributed to the equilibrium moisture content of the material. Each sample of the dried natural filler was then placed in a separate vial, and each vial was then placed in a larger jar containing some water. The large jar was then sealed and conditioned in an oven at 25°C or 70°C overnight. The conditioned natural filler samples were weighed again, and the moisture absorption values are shown in Table 6 below.
[0125] Table 6. Water absorption of selected natural fillers
[0126]
[0127] The samples conditioned at ambient temperature (25°C) recovered to a moisture content similar to the initially measured equilibrium moisture. However, the samples conditioned at elevated temperature (70°C) absorbed significantly more moisture.
[0128] To evaluate the effect of higher moisture content fillers, CA film samples containing 10% NF7 were prepared according to the above melt processing protocol and the formulations described in Table 1, Samples 40-41. Intermittent foaming of the film samples was performed according to the foaming protocol. The CA film of Sample 40 (dry condition) was not conditioned prior to foaming, while the CA film of Sample 41 (wet condition) was placed in a small jar, which was then placed in a large jar containing some water. The large jar was then sealed and conditioned at 70°C overnight prior to foaming.
[0129] Table 7. Density and cell size of dry and wet conditioned CA foams
[0130] sample condition Filler (wt%) <![CDATA[Density (g / cm 3 )]]> Pore size (nm) 40 dry NF7(10) 0.214 53±9 41 Wet NF7(10) 0.180 81±21
[0131] Table 7 demonstrates that preconditioning CA films containing hygroscopic natural fillers in a humid environment enables lower density foams with larger pore sizes. Since the natural fillers absorb moisture during the conditioning process, the moisture content of the film increases, and the absorbed moisture subsequently acts as a physical blowing agent to reduce the density of the foam.
[0132] Example 6 - Natural fillers as alternative nucleating agents (instead of talc)
[0133] Films containing various types of natural fillers were prepared according to the melt processing protocol described above and the formulations listed in Table 1, Samples 42-66. The film samples were then batch foamed according to the foaming protocol and Table 1. The resulting foam samples were evaluated for density and cell size.
[0134] The talc-free formulations of this example demonstrate that natural fillers can also be effectively used as nucleating agents. At loadings as low as 3%, several natural fillers exhibited adequate nucleation and foaming, resulting in low foam density and fine cell morphology. Foaming pressures of 100 and 130 bar appear to be the optimal conditions for producing low-density foams in the absence of inorganic nucleating agents.
[0135] In addition, natural fillers can be used in combination with talc to further reduce foam density, increase average cell size, and reduce the raw material cost of the composition. At low foaming pressures (50 and 70 bar), for most samples, the addition of 1 wt% talc increased foam density but reduced cell size. Surprisingly, at high foaming pressures (100 and 130 bar), the addition of 1 wt% talc significantly reduced foam density while increasing cell size.
[0136] Table 8. Comparison of density and cell size of foams containing 3% natural filler with and without nucleating agents at various pressures
[0137]
[0138]
Claims
1. A foamable composition comprising: 30 to 92 wt % cellulose acetate; 5 wt % to 30 wt % of at least one plasticizer; 3 wt % to 40 wt % of at least one natural filler; and 0 wt % to 9 wt % of at least one physical blowing agent; Wherein wt % is based on the total weight of the composition.
2. The foamable composition according to claim 1, wherein the cellulose acetate has an average degree of acetyl substitution in the range of 2.2 to 2.
6.
3. The foamable composition according to any one of claims 1-2, wherein the at least one plasticizer is selected from triacetin, triethyl citrate or polyethylene glycol.
4. A foamable composition according to any one of claims 1 to 3, wherein the natural filler is a biodegradable particulate material derived from a renewable organic source.
5. The foamable composition according to claim 4, wherein the natural filler is selected from pecan shell powder, walnut shell powder, wood powder, corn cob powder, rice husk powder, oat fiber powder or a combination thereof.
6. The foamable composition according to any one of claims 1 to 5, further comprising an inorganic physical nucleating agent.
7. The foamable composition according to any one of claims 1 to 5, which does not contain an inorganic physical nucleating agent.
8. A foamable composition according to any one of claims 1 to 7, wherein the natural filler has a maximum particle size of 50 to 600 microns.
9. The foamable composition according to any one of claims 1 to 8, wherein the natural filler further comprises up to 22 wt% water based on the dry weight of the natural filler.
10. The foamable composition according to any one of claims 1 to 9, further comprising a chemical foaming composition comprising: (a) a blowing agent, and (b) a carrier polymer having a melting point not exceeding 180°C.
11. The foamable composition of claim 10, wherein the foaming agent comprises sodium bicarbonate, sodium carbonate, citric acid, or a combination thereof.
12. A foamable composition according to any one of claims 10 to 11, wherein the carrier polymer is a biodegradable polymer.
13. The foamable composition of claim 12, wherein the carrier polymer comprises polybutylene succinate ("PBS"), polycaprolactone ("PCL"), polylactic acid ("PLA"), polyhydroxyalkanoate ("PHA"), polybutylene adipate terephthalate ("PBAT"), a starch derivative, poly(butylene succinate-co-succinate) ("PBSA"), or a combination thereof.
14. The foamable composition of any one of claims 12-13, wherein the carrier polymer is present at 25 wt% to 75 wt% based on the total weight of the chemically foamable composition.
15. The foamable composition according to any one of claims 1 to 14, in the form of a powder or granules.
16. A foam formed from the foamable composition of any one of claims 1 to 15, wherein the foam is biodegradable, industrially compostable or home compostable.
17. The foam of claim 16, wherein the foam has a g / cm 3 , or not more than 0.50g / cm 3 , or not more than 0.40g / cm 3 , or not more than 0.38g / cm 3 , or not more than 0.36g / cm 3 , or not more than 0.34g / cm 3 , or not more than 0.32g / cm 3 Or not more than 0.30g / cm 3 density.
18. The foam of any one of claims 16-17, wherein the foam has an average pore size of at least 40 μm, or at least 50 μm, or at least 60 μm, or at least 70 μm, or at least 80 μm, or at least 90 μm, or at least 100 μm, or at least 110 μm, or at least 120 μm, or at least 130 μm, or at least 140 μm, or at least 150 μm, or at least 160 μm, or at least 180 μm, or at least 200 μm, or at least 250 μm, or at least 300 μm, or at least 350 μm, or at least 400 μm, or at least 450 μm, or at least 500 μm, or at least 550 μm, or at least 600 μm.
19. The foam of any one of claims 16-19, wherein the foam does not contain an inorganic particulate component.
20. The foam of any one of claims 16-19, wherein the article is a thermoformed foam article or a molded foam article.